Capital depreciation allowances, redistributive taxation, and economic growth - Günther Rehme (Journal of Public Economic Theory, 2022)
Are capital depreciation allowances when coupled with capital income taxes good instruments for redistribution in the long run? In a simple two-agent-economy I find that accelerated depreciation is good for growth, but bad for redistribution. The opposite holds for capital income taxes. However, in a feedback Stackelberg equilibrium, where the government is the leader and the private sector the follower, the depreciation allowance is maximal in the long run, time-consistent optimum. This removes the accumulation distortion of capital income taxes. Furthermore, the latter, and so redistribution, is found to be generically nonzero in the time-consistent optimum, and depends on the social weight of transfers receivers, the pretax factor income distribution, the intertemporal elasticity of substitution and the time preference rate. Thus, accelerated depreciation allowances are an important indirect tool for redistribution. The tax scheme allows for a separation of “efficiency” and “equity” concerns for redistributive policies.
Keywords: 330